Integration of Textural and Material Information into BIM Using Spectrometry and Infrared Sensing - Zabin, Asem Ahmad (2015)
A Master of Science thesis in Civil Engineering by Asem Ahmad Zabin entitled, "Integration of Textural and Material Information into BIM Using Spectrometry and Infrared Sensing," submitted in May 2015. Thesis advisor is Dr. Tarig Ali. Soft and hard copy available.